Genetic dissection of maydis leaf blight resistance in maize through QTL mapping - Bhupender Kumar; Rakhi Singh; Shrikant Yankanchi; Pardeep Kumar; Pushpendra Pushpendra; Pravin Bagaria; Robin Gogoi; Prahlad Piyal; Neelam Sunil; Ajay Kumar (Molecular Biology Reports, 2026)

Development of a CRISPR/dCas9-based membrane-assisted colorimetric assay for detection of high-risk HPV16 and HPV18: a proof-of-concept study - Vaibhav Kumar Tamrakar; Kuldeep Sharma; Pushpendra Singh; Anudita Bhargava; Pushpawati Thakur; Sanjay Singh Negi (Molecular Biology Reports, 2026)

Therapeutic Evaluation of Kaempferol-loaded Liposomes in Hepatocellular Carcinoma through i-NOS/e-NOS/p53/Caspase-Mediated Apoptotic Pathway - Naina Srivastava; Pranesh Kumar; Pushpendra Kumar Tripathi (Journal of Pharmaceutical Innovation, 2026)

Integrated dendrochemical analyses and standardized environmental indicators for reconstructing historical trace elemental pollution in Asia: a systematic review - Wagmare Balraju; Mayank Shekhar; Pushpendra Pandey; Devi Lal; Rupesh Dhyani; Amalava Bhattacharyya; Anupam Sharma (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

An integrated framework for assessing human interventions, climate change, and water resilience in the Northeastern India - Vishal Singh; Pushpendra Kumar Singh; Deepti Rani; Surjeet Singh; Sudhir Kumar Singh (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Microalgal diversity in correlation with physicochemical properties and water quality of Alaknanda River of Garhwal Region, Uttarakhand - Rahul Goswami; Pushpendra Singh Rawat; Rahul Negi; Prakash Bhuyar; Tawan Chatsungnoen; Gaanty Pragas Maniam; Natanamurugaraj Govindan (Next Research, 2026)

Ecological assembly of cereal root endophytic bacteriomes in two contrasting arid agroecosystems - Udita Pushpad; Ritwika Das; Pushpendra Sharma; Priyanka Kumari; Minakshi Grover; Rajeev Kaushik (Applied Soil Ecology, 2026)

Multidimensional genetic analysis of bread wheat (Triticum aestivum L.) germplasm for precision breeding - Ritu Rani; Pradeep Kumar Sharma; Jitendra Kumar; Pushpendra; Rahul Kumar; Sushil Kumar; Priyanka Veerala; Prashant Kaushik (Ecological Genetics and Genomics, 2026)

A hydration-scaffold framework for phase-sensitive coupling and collective organization in biomolecular water - Pushpendra Singh; Anirban Bandyopadhyay (BioSystems, 2026)

Simplified Inhouse Nanoweb Membrane Enrichment Coupled Viral Whole Genome Shotgun Metagenomics Approach for Waste Water Surveillance - Shashi Sharma; Pushpendra Kumar Sharma; Ekta Gupta; Paban Kumar Dash; Ambuj Srivastava (Food and Environmental Virology, 2026)

Bioprospecting osmotolerant phyllosphere bacteria: functional characterization and biotechnological application for enhanced nutrient use efficiency in solanum crops - Satish Kumar; Meena Rathore; Pushpendra Sharma; Minakshi Grover; Rajeev Kaushik (World Journal of Microbiology and Biotechnology, 2026)

Comprehensive overview of the multifaceted roles of non-structural proteins of Orthoflavivirus in replication and immunopathology - Chirantan Maity; Souvik Mitra; Anjali Tripathi; Samyak Khobdagade; Chandhu Balachandran; Pushpendra Singh (Virus Genes, 2026)

Molecular basis of fertility restoration: roles of Rf, RFL, PPR, and mTERF genes in wheat and other cereal crops - Pushpendra K. Gupta; Harindra S. Balyan; Sourabh Kumar (Euphytica, 2026)

Potential of competitive and efficient Mesorhizobium strains to improve chickpea growth, yield, and soil health - Venkatesh Kokila; Samia Saleem; Shiv Charan Kumar; Pushpendra Tiwari; Sindhunath Chakraborty; Murugan Kumar; Hillol Chakdar; Alok Kumar Srivastava; Anil Kumar Saxena (Symbiosis, 2026)

Nutrient heterogeneity shapes bacterial diversity and functions in wheat fields of the Lower Indo-Gangetic Plain - Sindhunath Chakraborty; Murugan Kumar; Waquar Akhter Ansari; Shiv Charan Kumar; Pushpendra Tiwari; Hillol Chakdar; Mohammad Samir Farooqi; Sudhir Srivastava; Anu Sharma; Girish Kumar Jha; Alok Kumar Srivastava (Rhizosphere, 2026)

Next generation silver nanoweb-carbon composite for protection against chem-bio threat and toxic industrial gases - Akash Verma; Pushpendra K. Sharma; Virendra Vikram Singh; Lokesh K. Pandey; Vikas B. Thakare; Kavita Agarwal; Sanjay Upadhyay (Environmental Science and Pollution Research, 2026)

Twenty years of wheat genomics (2005–2025) - Pushpendra Kumar Gupta (Trends in Plant Science, 2026)

In-silico characterization and expression analysis of the Waxy gene in rice (Oryza sativa L.) - Ali Sina Jayhoon; Pushpendra Kumar (Cereal Research Communications, 2026)

Development of a synergistic tripartite consortium and hybrid growth media for enhanced methane oxidation and assessment of in vitro plant growth-promoting traits - C S Shivaranjan; Shivani Kaushik; Pushpendra Sharma; Arti Bhatia; Radha Prasanna; Rajeev Kaushik (World Journal of Microbiology and Biotechnology, 2026)

Arsenate adsorption onto hydrous ferric oxide: Insights from triple layer surface complexation modeling - Hafsa Nazir; Raheena Moozhikkal; Bhawna Thakur; Shray Pathak; Pushpendra P. Singh (Journal of Geochemical Exploration, 2026)

Low-carbon cement strategy: utilizing fly ash to enhance jarosite-modified OPC performance - Rajpal Singh Shekhawat; Pushpendra Kushwaha; Madhu Agarwal (Innovative Infrastructure Solutions, 2026)

Study of Aerosols Optical Depth and Ångström Exponent Over IGP: A Case Study - Pushpendra Singh Soni; Vikram Singh; Alok Sagar Gautam; Amar Deep; Rolly Singh; Alka Gautam; Sneha Gautam; Surendra Pratap Singh (Aerosol Science and Engineering, 2026)

Experimental study of a solar active space heating system with cascaded PCM energy storage for sustainable off-grid use in cold climates - Pushpendra Kumar Shukla; Ajit Kumar; P. Anil Kishan (Energy and Buildings, 2026)

Exploring genetic variability and its association with growth traits in Rohilkhandi goats - Nitish Gaitri; Subodh Kumar; Pushpendra Kumar; Amit Kumar; Hari Om Pandey (Tropical Animal Health and Production, 2026)

Willingness to pay for demand for improvement in drinking water, sanitation, and micro-environmental facilities: case study from Lucknow slums in India - Sanatan Nayak; Pushpendra Kumar Singh (Environment, Development and Sustainability, 2026)

Isolation, structural characterisation and in silico evaluation of new biflavonoids from Ficus racemosa L. - Suman Lata; Pushpendra Koli; Sultan Singh; Brijesh Kumar Bhadoria (Natural Product Research, 2026)

Why carbon offsets may fail in complex systems: A causal inference perspective - Pushpendra Rana; Forrest Fleischman; Amit Sharma (Environmental Science & Policy, 2026)

Therapeutic potential of plant-derived tannic acid on pulmonary disorders in experimental models - Yokeshwaran Punniyasekaran; Bhagyashree Meena; Harsha Akshaylal Pal; Pushpendra Kumar Namdeo; Sudhakar Gandhi Paramasivam; Subbiah Rajasekaran (Inflammopharmacology, 2026)

Exogenous Melatonin Delays Ripening and Maintains Quality of Pineapple During Postharvest Storage - Pushpendra Kumar; Swarajya Laxmi Nayak; Arpan Bhowmik (Applied Fruit Science, 2026)

Transition of Cropping Systems Influences Nutrient Stability, Microbial Diversity and Soil Quality in the Upper Indo-Gangetic Plains of India - S. R. Singh; Pushpendra Pratap Singh Yadav; Achal Singh; Sanjeev Kumar (Journal of Soil Science and Plant Nutrition, 2026)

Tree-ring evidence marks year 2022 as the driest spring season in nearly four centuries in the Western Himalayas - Pushpendra Pandey; Moetasim Ashfaq; Devi Lal; Mayank Shekhar; Bhupendra Bahadur Singh; Parminder Singh Ranhotra; Pritam Chand; Amalava Bhattacharyya (Science of The Total Environment, 2026)

Multifunctional endospermic bacteria from cultivars of Triticum durum & T. dicoccum influencing plant growth - Jogdande SaiPrasad; Archna Suman; Dharmendra Kumar; Pushpendra Sharma (Archives of Microbiology, 2026)

Dynamic performance evaluation of evolutionary multi-objective optimization algorithms for gait cycle optimization of a 25-DOFs NAO humanoid robot - Pushpendra Gupta; Dilip Kumar Pratihar; Kalyanmoy Deb (Swarm and Evolutionary Computation, 2025)

Forest-stand structure and treeline dynamics of Himalayan Fir over the last four centuries in Kashmir, western Himalaya - Stuti Jain; Bency David Chinthala; Parminder Singh Ranhotra; Pushpendra Pandey; Mayank Shekhar; Jussi Grießinger; Rajesh Joshi; Maroof Hamid; Firdous A. Dar; Faizan Shafee; Anzar Ahmad Khuroo; Chandra Prakash Singh; et al. (Dendrochronologia, 2025)

Corrigendum to “Biomarker identification in warehouse beetle (Trogoderma variabile) larvae: Tracking metabolic shifts across grain hosts” [Biochem. Systemat. Ecol. 120 (2025) 104983] - Thamer Al-Shuwaili; Khalid Mohammed; Pushpendra Koli; Sonu Kumar Mahawer; Anup Kumar (Biochemical Systematics and Ecology, 2025)

Exploring genetic polymorphisms and their association with reproductive traits in Rohilkhandi goats - Nitish Gaitri; Subodh Kumar; Pushpendra Kumar; Amit Kumar; Hari Om Pandey; Roshni Chand (Tropical Animal Health and Production, 2025)

Conditional QTL analysis of grain yield and eight yield-contributing traits under drought stress in wheat (Triticum aestivum L.) - Vijay Gahlaut; Vandana Jaiswal; Harindra Singh Balyan; Pushpendra Kumar Gupta (Plant Physiology Reports, 2025)

Expression profile analysis of estrous-phased ovarian tissue of high and low prolific lines of inbred Swiss albino mice - Babu Lal Saini; Amit Kumar; Sheikh Firdous Ahmad; Arnav Mehrotra; Shweta Sachan; Rohit Singh; Jai Prakash; Anuj Chauhan; Triveni Dutt; Pushpendra Kumar (Molecular Biology Reports, 2025)

Preface to the Big data analytics and machine learning in water resources - Sudhir Kumar Singh; Pushpendra Singh; Dharmaveer Singh; Shiyin Liu; Vishal Singh (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Exploring influential parameters affecting residential building energy use: advancing energy efficiency through machine learning - Pushpendra Kr. Chaturvedi; Nand Kumar; Jørn Toftum; Rune Korsholm Andersen; Ravita Lamba; Kedar Mehta (Clean Technologies and Environmental Policy, 2025)

Mitigating drought stress in wheat: growth promotion and physiological adaptations induced by root endophytic bacteria isolated from hot and cold arid desert agroecosystems of India - Udita Pushpad; Pushpendra Sharma; Minakshi Grover; Rajeev Kaushik (World Journal of Microbiology and Biotechnology, 2025)

Tree‐Ring‐Based Drought Reconstruction Reveals Increased Pre‐Monsoon Droughts Over the Past Two Centuries in the Lug Valley Kullu, Northwest Himalayas - Devi Lal; Pushpendra Pandey; Mayank Shekhar; Pritam Chand; Rupesh Dhyani; Ishtiaq Ahmed; Rinku Kumar; Amalava Bhattacharyya; Parminder Singh Ranhotra (International Journal of Climatology, 2025)
Understanding of long‐term drought variability in the Himalayan region is crucial for sustainable water resource management and climate adaptation. We analysed the self‐calibrated Palmer Drought Severity Index (scPDSI) based on a well‐established “signal‐free” standardised tree‐ring width (TRW) chronology of Cedrus deodara (Roxb. ex D.Don) G.Don (deodar) from Lug Valley of Kullu district of Himachal Pradesh, Northwest Himalayas. Tree growth climate analysis indicated that the pre‐monsoon precipitation and the scPDSI positively affected the radial growth, whereas temperature had a negative influence. The strongest correlation between the scPDSI and TRW chronology ( r = 0.636, p n = 114) during the March, April, and May (MAM) period indicates that the pre‐monsoon drought scPDSI‐MAM is the dominant growth‐limiting factor. Using a linear regression model, we reconstructed drought variability back to 1793 ce , explaining 40.5% of the total variance. The reconstruction identified prolonged drought periods (1794–1825, 1888–1980, and 2000–2010) with increasing frequency and intensity in recent decades, while pluvial conditions prevailed during 1825 to 1875 and 1982 to 1998. The multi‐taper method spectral analysis identified the presence of both low and high frequency cycles of 80, 33, 6, 2.3, and 2 years within the reconstructed time series, indicating periodic climatic variability. Spatial correlation with tropical sea surface temperatures indicates strong teleconnections with global climate drivers like the El Niño–Southern Oscillation, Pacific Decadal Oscillation, and Atlantic Multidecadal Oscillation. These findings underscore the rising threat of pre‐monsoon droughts to regional hydrology, agriculture, and socio‐economic stability. As droughts become more frequent, proactive policies and adaptive strategies are essential to minimise future risks acorss this region.

MicroRNAs associated with spot blotch in bread wheat (Triticum aestivum) - Neeraj Kumar Vasistha; Sandeep Sharma; Vinod Kumar Mishra; Tinku Gautam; Gautam Saripalli; Sunita Pal; Pushpendra Kumar Gupta (Physiological and Molecular Plant Pathology, 2025)

Multi-objective optimization of glazing and shading configurations for visual, thermal, and energy performance of cooling dominant climatic regions of India - Pushpendra Kr. Chaturvedi; Nand Kumar; Ravita Lamba; Kedar Mehta (Clean Technologies and Environmental Policy, 2025)

Diversity and distribution of arbuscular mycorrhizal fungi in phosphorus-deficient acidic soils of Northeast India: implications for sustainable agriculture - Priya Murugesan; Pushpendra Sharma; Subrata Nath Bhowmik; Samik Chowdhury; Rajeev Kaushik (World Journal of Microbiology and Biotechnology, 2025)

Attenuation characteristics of mechanical vibrations and its effect on heritage structures of Chittorgarh Fort Complex, India - Harsh Kr Verma; Ashok Kr Singh; Pushpendra Patel; Rahul Verma (Journal of Earth System Science, 2025)

Monsoon dynamics and future projections in the Himalaya: Insights into sea surface temperature, sea level pressure relationships, and future flood risks - Mayank Shekhar; Pushpendra Pandey; Shaktiman Singh; Anupam Sharma (Dynamics of Atmospheres and Oceans, 2025)

Biomarker identification in warehouse beetle (Trogoderma variabile) larvae: Tracking metabolic shifts across grain hosts - Thamer Al-Shuwaili; Khalid Mohammed; Pushpendra Koli; Sonu Kumar Mahawer; Anup Kumar (Biochemical Systematics and Ecology, 2025)

Temporal and Spatial Variations in Lightning Activity and Meteorological Parameters Across the Indian Himalayan Region and Indo-Gangetic Plains - Rolly Singh; Vikram Singh; Alok Sagar Gautam; Sanjeev Kumar; Karan Singh; Pushpendra Singh Soni; Alka Gautam; Sneha Gautam (Asia-Pacific Journal of Atmospheric Sciences, 2025)

Prospective Life Cycle Assessment and upscaling of an emerging biorefinery process: A case study on methyl ketone - Pushpendra; Andreas Schonhoff; Stefan Christian Füchsl; Hubert Röder; Petra Zapp (Journal of Cleaner Production, 2025)

Long-term effect of Bt cottonseed cake on nutrient utilisation, growth performance and health of rams in tropical conditions - Krishan Kunwar Singh; Pushpendra Koli; Sultan Singh; Vijay Kumar Yadav; Asim Kumar Misra; Subhendu Bikas Maity; P. Govindraj; R. Karuppiyan (Tropical Animal Health and Production, 2025)

Mitigating enteric methane emissions with Madhuca longifolia phenolic extract supplementation in forages and diets through in vitro fermentation to support climate-resilient livestock production - Sultan Singh; Pushpendra Koli; Brijesh Kumar Bhadoria; Yonglin Ren (Journal of Environmental Management, 2025)

Implementation of satellite-based water accounting plus (WA+) framework for estimating groundwater balance and utilization in a semi-arid river basin of India - Debrupa Chatterjee; Pushpendra Kumar Singh; Dharmaveer Singh; Diganta Bhusan Das (Groundwater for Sustainable Development, 2025)

Transcriptome analysis for the identification of spot blotch responsive genes and miRNAs in wheat - Neeraj Kumar Vasistha; Archita Tandon; Sunita Pal; Sandeep Sharma; Vinod Kumar Mishra; Pushpendra Kumar Gupta (Physiological and Molecular Plant Pathology, 2025)

Investigation of radon and thoron exhalation rates in soils: Manali-Leh Highway region of Himalayas - Jyoti Yadav; Rajat Parkash; Bhupesh Khyalia; R.P. Chauhan; Pushpendra P. Singh; Paramjeet Singh; Ranjeet Dalal (Journal of Environmental Radioactivity, 2024)

Identification and characterization of sulphotransferase (SOT) genes for tolerance against drought and heat in wheat and six related species - Jyoti Chaudhary; Himanshi Gangwar; Vandana Jaiswal; Pushpendra Kumar Gupta (Molecular Biology Reports, 2024)

Assessment of natural radioactivity in the Higher and Tethys Himalayan Rocks along Manali-Leh Highway, India - Jyoti Yadav; Rajesh Beniwal; Pushpendra P. Singh; Paramjeet Singh; Ranjeet Dalal (Environmental Monitoring and Assessment, 2024)

Genetic Diversity and Functional Potential of Streptomyces spp. Isolated from Pachmarhi Biosphere Reserve, India - Pushpendra Tiwari; Waquar Akhter Ansari; Shiv Charan Kumar; Praveen Kumar Tiwari; Murugan Kumar; Hillol Chakdar; Alok Kumar Srivastava; Anil Kumar Saxena; Laishram Shantikumar (Current Microbiology, 2024)

Experimental analysis of thermal energy efficient clay brick incorporated with phase change material and insulation - Pushpendra Kumar Singh Rathore; Bhaskar Patel; Manglesh Kumar Gupta; Basant Singh Sikarwar; R.K. Sharma (Process Safety and Environmental Protection, 2024)

Investigation of radioactivity and heavy metal levels in soil samples from neutral and vegetation land of Punjab, India - Sanjeet S. Kaintura; Swati Thakur; Sarabjot Kaur; Soni Devi; Katyayni Tiwari; Priyanka; Arzoo Sharma; Pushpendra P. Singh (Environmental Monitoring and Assessment, 2024)

Are the ecosystem-level evaporative stress indices representative of evaporative stress of vegetation? - Pushpendra Raghav; Mukesh Kumar (Agricultural and Forest Meteorology, 2024)

Effect of high temperature stress on metabolome and aroma in rice grains - Anurag Mishra; Braj Bhushan Singh; Najam Akhtar Shakil; M.D. Shamim; Fozia Homa; Rajat Chaudhary; Prashant Yadav; Deepti Srivastava; Parveen Fatima; Vandana Sharma; Manoj Kumar Yadav; Pushpendra Kumar (Plant Gene, 2024)

A variable-order fractional mathematical model for the strategy to combat the atmospheric level of carbon dioxide - Pushpendra Kumar; Vedat Suat Erturk (Modeling Earth Systems and Environment, 2024)

Systematic Development of Hot Melt Extrusion-Based Amorphous Solid Dispersion: Integrating Quality by Design and In Silico Modeling - Anuj Kumar Fanda; Ajinkya Jadhav; Pushpendra S. Naruka; Dhwani Rana; Derajram Benival (Journal of Pharmaceutical Innovation, 2024)

Efficient extraction of metals (Fe, Zn, Pb) from hazardous jarosite using ionic liquid and waste-derived solvents - Pushpendra Kushwaha; Madhu Agarwal (Environmental Science and Pollution Research, 2024)

Temporal dynamics of urban air pollutants and their correlation with associated meteorological parameters: an investigation in northern Indian cities - Pushpendra Singh Soni; Vikram Singh; Alok Sagar Gautam; Karan Singh; Manish Sharma; Rolly Singh; Alka Gautam; Surendra Pratap Singh; Sanjeev Kumar; Sneha Gautam (Environmental Monitoring and Assessment, 2024)

Impact of Edible Hydrocolloids on Quality and Shelf Life of Litchi (Litchi chinensis Sonn.) Under Ambient Conditions - Pushpendra Kumar; Shruti Sethi; Swarajya Laxmi Nayak (Applied Fruit Science, 2024)

A novel partitioning of gross primary production and water use efficiency for sustaining water and food security using Budyko hypothesis - Debrupa Chatterjee; Pushpendra Kumar Singh; Dharmaveer Singh; Vijay P. Singh (Science of The Total Environment, 2024)

A comprehensive profile of SARS-CoV-2 variants spreading during the COVID-19 pandemic: a genomic characterization study from Chhattisgarh State, India - Sanjay Singh Negi; Kuldeep Sharma; Anudita Bhargava; Pushpendra Singh (Archives of Microbiology, 2024)

Hurdle approach for enhancing storage life of minimally processed apple slices using active modified atmosphere packaging - Pushpendra Kumar; Shruti Sethi; Eldho Varghese (Acta Physiologiae Plantarum, 2024)

Rhizospheric Trichoderma harzianum TBR-7 in combination with chitosan for eco-friendly management of crown rot disease in Egyptian clover (Trifolium alexandrinum L.) - Nitish Rattan Bhardwaj; Maneet Rana; Pushpendra Koli; Rahul Kaldate; Ajoy Kumar Roy; Amaresh Chandra (European Journal of Plant Pathology, 2023)

Comparative analysis of VMT genes/proteins in selected plant species with emphasis on bread wheat (Triticum aestivum L.) - Hemant Sharma; Shayaba; Rahul Kumar; Jitendra Kumar; Deepa Bhadana; Ritu Batra; Rakhi Singh; Sachin Kumar; Joy K Roy; Harindra S. Balyan; Pushpendra K. Gupta (Genes & Genomics, 2023)

Performance evaluation of different gridded precipitation and CMIP6 model products with gauge observations for assessing rainfall variability under the historical and future climate change scenario over a semi-arid catchment, India - Debrupa Chatterjee; Dharmaveer Singh; Pushpendra Kumar Singh; Nicola Fohrer; Bhupendra Bahadur Singh (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Mosaic Recombination Inflicted Various SARS-CoV-2 Lineages to Emerge into Novel Virus Variants: a Review Update - Pushpendra Singh; Kuldeep Sharma; Dipika Shaw; Anudita Bhargava; Sanjay Singh Negi (Indian Journal of Clinical Biochemistry, 2023)

Medicinal plants, phytoconstituents and traditional formulation as potential therapies for SARS-CoV-2: a review update - Pushpendra Singh; Manish Kumar Tripathi; Kuldeep Sharma; Anudita Bhargava; Sanjay Singh Negi (Vegetos, 2023)

Identification and characterization of RuvBL DNA helicase genes for tolerance against abiotic stresses in bread wheat (Triticum aestivum L.) and related species - Jyoti Chaudhary; Tinku Gautam; Vijay Gahlaut; Kalpana Singh; Sourabh Kumar; Ritu Batra; Pushpendra Kumar Gupta (Functional & Integrative Genomics, 2023)

Production of ethanol, lipid and lactic acid from mixed agrowastes hydrolysate - Jyoti Singh; Abha Sharma; Pushpendra Sharma; Govind Singh Tomar; Minakshi Grover; Surender Singh; Lata Nain (Natural Product Research, 2023)

Investigations on the hydrological impacts of climate change on a river basin using macroscale model H08 - Pushpendra Raghav; T I Eldho (Journal of Earth System Science, 2023)

Further studies on nicotianamine aminotransferase (NAAT) genes involved in biofortification in bread wheat (Triticum aestivum L.) - Tinku Gautam; Irfat Jan; Ritu Batra; Kalpana Singh; Renu Pandey; Pradeep Kumar Sharma; Harindra Singh Balyan; Pushpendra Kumar Gupta (Plant Gene, 2023)

Pharmacognostic and Nutraceutical Potential of Momordica Dioica Roxb. Ex willd. Fruit - Akanksha Srivastava; Ankita Misra; Mridul Kant Chaudhary; Pushpendra Kumar Shukla; Manish Kumar; Sharad Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Temporal and Spatial Variations of Satellite-Based Aerosol Optical Depths, Angstrom Exponent, Single Scattering Albedo, and Ultraviolet-Aerosol Index over Five Polluted and Less-Polluted Cities of Northern India: Impact of Urbanization and Climate Change - Rolly Singh; Vikram Singh; Alok Sagar Gautam; Sneha Gautam; Manish Sharma; Pushpendra Singh Soni; Karan Singh; Alka Gautam (Aerosol Science and Engineering, 2023)

Water accounting of a trans-boundary river basin using satellite observations and WA+ framework - Nirmal Kumar; Sudhir Kumar Singh; Pushpendra K. Singh; Dilip Kumar Gautam; Pooja Patle; H.K. Pandey; Pankaj Chauhan (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Utilization of metal industry solid waste as an adsorbent for adsorption of anionic and cationic dyes from aqueous solution through the batch and continuous study - Pushpendra Kushwaha; Madhu Agarwal (Environmental Science and Pollution Research, 2023)

Exploring limits to tree planting as a natural climate solution - Pushpendra Rana; Lav R. Varshney (Journal of Cleaner Production, 2023)

QTL analysis for nitrogen use efficiency in wheat (Triticum aestivum L.) - Rakhi Singh; Gautam Saripalli; Anuj Kumar; Tinku Gautam; Susheel Kumar Singh; Vijay Gahlaut; Sachin Kumar; Prabina Kumar Meher; Rajendra Prasad Mishra; Vinod Kumar Singh; Pradeep Kumar Sharma; Harindra Singh Balyan; et al. (Euphytica, 2023)

Influence of water use efficiency parameterizations on flux variance similarity-based partitioning of evapotranspiration - Pradeep Wagle; Pushpendra Raghav; Mukesh Kumar; Stacey A. Gunter (Agricultural and Forest Meteorology, 2023)

Characterization of homogenous acid catalyzed biodiesel production from palm oil: experimental investigation and numerical simulation - Digambar Singh; Dilip Sharma; Pushpendra Kumar Sharma; Amit Jhalani; Dinesh Kumar Sharma (Environmental Science and Pollution Research, 2022)

Cow-urine emulsified diesel fuel: preparation, stability, and rheological study for diesel engine application - Amit Jhalani; Sumit Sharma; Digambar Singh; Pushpendra Kumar Sharma (Environmental Science and Pollution Research, 2022)

Bearing capacity of strip footings on jointed rock mass - Manendra Singh; Manohar Narayan Viladkar; Pushpendra Singh Shekhawat; Kartikeya Tripathi; Milind Amin (Arabian Journal of Geosciences, 2022)

Exploration of allelic variants in short tandem repeats (STRs) flanking milk production QTLs and their association with milk production traits in Indian water buffaloes - A. Vani; Subodh Kumar; Sanjeev Kumar; Anuj Chauhan; Nihar Ranjan Sahoo; Med Ram Verma; A. K. S. Tomar; Pushpendra Kumar (Tropical Animal Health and Production, 2022)

Species distribution modeling and assessment of environmental drivers responsible for distribution and preferred niche of critically endangered and endemic ornamental freshwater fish species of the genus Sahyadria - Ajey Kumar Pathak; Pushpendra Verma; Rajesh Dayal; Uttam Kumar Sarkar (Environmental Science and Pollution Research, 2022)

Intraspecific Variation in Gloriosa Superba (L.) Population from Western Himalayas (India) and Evaluation of in vitro Antigout Potential - Ankita Misra; Pushpendra Kumar Shukla; Manish Kumar; Poonam Rawat; Sharad Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Characterization of Ustilaginoidea virens causing rice false smut and its bio-control in north India - Sanjay Kumar Goswami; Chhavi Thakur; Prassan Choudhary; Shaloo Verma; Pushpendra Tiwari; Sudipta Das; Mohammad Shahid; Bansh Narayan Singh; Hillol Chakdar; M. Kumar; A. K. Srivastava; A. K. Saxena (Indian Phytopathology, 2022)

BS-Seq reveals major role of differential CHH methylation during leaf rust resistance in wheat (Triticum aestivum L.) - Kalpana Singh; Gautam Saripalli; Tinku Gautam; Pramod Prasad; Neelu Jain; Harindra Singh Balyan; Pushpendra Kumar Gupta (Molecular Genetics and Genomics, 2022)

GWAS for main effects and epistatic interactions for grain morphology traits in wheat - Parveen Malik; Jitendra Kumar; Shiveta Sharma; Prabina Kumar Meher; Harindra Singh Balyan; Pushpendra Kumar Gupta; Shailendra Sharma (Physiology and Molecular Biology of Plants, 2022)

Meta-QTLs, ortho-MetaQTLs and candidate genes for grain Fe and Zn contents in wheat (Triticum aestivum L.) - Rakhi Singh; Gautam Saripalli; Tinku Gautam; Anuj Kumar; Irfat Jan; Ritu Batra; Jitendra Kumar; Rahul Kumar; Harindra Singh Balyan; Shailendra Sharma; Pushpendra Kumar Gupta (Physiology and Molecular Biology of Plants, 2022)

Potent γ-amino butyric acid producing psychobiotic Lactococcus lactis LP-68 from non-rhizospheric soil of Syzygium cumini (Black plum) - Pushpendra Sharma; Neera Singh; Surender Singh; Sunil Kumar Khare; Pawan Kumar Singh Nain; Lata Nain (Archives of Microbiology, 2022)

Correction to: Notes on the typification of four Himalayan aconites - Priyanka Agnihotri; Danish Husain; Pushpendra Katiyar; Tariq Husain (Kew Bulletin, 2021)

Correction to: WheatQTLdb: a QTL database for wheat - Kalpana Singh; Ritu Batra; Shiveta Sharma; Gautam Saripalli; Tinku Gautam; Rakhi Singh; Sunita Pal; Parveen Malik; Manoj Kumar; Irfat Jan; Sahadev Singh; Deepak Kumar; et al. (Molecular Genetics and Genomics, 2021)

Meta-QTLs, ortho-MQTLs and candidate genes for nitrogen use efficiency and root system architecture in bread wheat (Triticum aestivum L.) - Dinesh Kumar Saini; Yuvraj Chopra; Neeraj Pal; Amneek Chahal; Puja Srivastava; Pushpendra Kumar Gupta (Physiology and Molecular Biology of Plants, 2021)

Genetic analysis of human papilloma virus 16 E6/E7 variants obtained from cervical cancer cases in Chhattisgarh, a central state of India - Sanjay Singh Negi; Kuldeep Sharma; Divakar Sharma; Pushpendra Singh; Pragya Agarwala; Nighat Hussain; Anudita Bhargava; Padma Das; Sarita Agarwal (VirusDisease, 2021)

WheatQTLdb: a QTL database for wheat - Kalpana Singh; Ritu Batra; Shiveta Sharma; Gautam Saripalli; Tinku Gautam; Rakhi Singh; Sunita Pal; Parveen Malik; Manoj Kumar; Irfat Jan; Sahadev Singh; Deepak Kumar; et al. (Molecular Genetics and Genomics, 2021)

Variability in alkaloid and phenolic content vis-a-vis antigout potential among the natural population of Gloriosa superba (L.) collected from Central India - Ankita Misra; Sharad Srivastava; Pushpendra Kumar Shukla; Manish Kumar; Md. Khalid; Poonam Kushwaha; Pawan Kumar Agrawal (Natural Product Research, 2021)

Pharmacognostical, Antioxidative Activity Associated with Phytochemical of Eucalyptus globulus Labill. and Evaluation of in vitro Antidiabetic Potential - Namrata Dwivedi; Pushpendra Kumar Shukla; Ruchika Sharma; Indra Prasad Tripathi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

An efficient method for identification of epileptic seizures from EEG signals using Fourier analysis - Virender Kumar Mehla; Amit Singhal; Pushpendra Singh; Ram Bilas Pachori (Physical and Engineering Sciences in Medicine, 2021)

Correction to: QTL analysis and fine mapping of a QTL for yield‑related traits in wheat grown in dry and hot environments - Habtamu Tura; James Edwards; Vijay Gahlaut; Melissa Garcia; Beata Sznajder; Ute Baumann; Fahimeh Shahinnia; Matthew Reynolds; Peter Langridge; Harindra Singh Balyan; Pushpendra K. Gupta; Thorsten Schnurbusch; et al. (Theoretical and Applied Genetics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00122-021-03792-4

Rhamonolipids produced by Pseudomonas aeruginosa promotes methane hydrates formation in fixed bed silica gel medium - Amit Arora; Swaranjit Singh Cameotra; Chandrajit Balomajumder; Rajnish Kumar; Anil Kumar Singh; B. Santhakumari; Pushpendra Kumar; Sukumar Laik (Marine Geophysical Research, 2021)

A Comprehensive Review on 1st-Generation Biodiesel Feedstock Palm Oil: Production, Engine Performance, and Exhaust Emissions - Digambar Singh; Dilip Sharma; S. L. Soni; Chandrapal Singh Inda; Sumit Sharma; Pushpendra Kumar Sharma; Amit Jhalani (BioEnergy Research, 2021)

Parametric study to design competent irregular-shaped remnants in mechanised depillaring - Pushpendra Sharma; Ashok Kumar; Noorullah Shams; Amit Kumar Verma; Dheeraj Kumar; Arun Kumar Singh; Sahendra Ram (Arabian Journal of Geosciences, 2021)

Revamping extended range forecast of Indian summer monsoon - Pushpendra Raghav; Swatah Snigdha Borkotoky; Jisha Joseph; Rajib Chattopadhyay; A. K. Sahai; Subimal Ghosh (Climate Dynamics, 2020)

A case study on the rockfall assessment and stability analysis along Lengpui-Aizawl highway, Mizoram, India - Sahil Sardana; Pushpendra Sharma; Amit Kumar Verma; Trilok Nath Singh (Arabian Journal of Geosciences, 2020)

An assessment of global satellite‐based precipitation datasets in capturing precipitation extremes: A comparison with observed precipitation dataset in India - Vivek Gupta; Manoj K. Jain; Pushpendra K. Singh; Vishal Singh (International Journal of Climatology, 2020)
The availability of global satellite‐based precipitation datasets provides an asset to accomplish precipitation dependent analysis where gauge based precipitation datasets are not available or limited. In this study, we have taken three most popular and globally accepted satellite‐based daily gridded (0.25° × 0.25°) precipitation datasets such as Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), Satellite Soil Moisture to Rain (SM2RAIN‐ASCAT) and Tropical Rainfall Measuring Mission (TRMM now available as Global Precipitation Measurement [GPM]) for 10 years (2007–2016) time‐series durations to test their reliability across India. The India Meteorological Department (IMD) observed daily gridded (0.25° × 0.25°) precipitation data have been taken as reference data to compare the other three satellite‐based gridded precipitation datasets by developing standard extreme precipitation indices (SEPIs). The precipitation extremity has been tested in the wet season (June–July–August–September) and throughout the year. We have also analysed the extreme behaviour of precipitation (in both upper and lower tails) using quantile‐quantile (Q–Q) regression analysis after selecting 33 random precipitation grids across India. The overall analysis results showed that all satellite‐based datasets have significant spatial heterogeneity in estimating precipitation extremes accurately which varies across India. Among all satellite‐precipitation datasets, TRMM found closer to IMD than SM2RAIN‐ASCAT and CHIRPS. The frequency based SEPIs showed that CHIRPS, TRMM and SM2RAIN‐ASCAT have similarities to IMD precipitations. The intensity‐based SEPIs show that TRMM and CHIRPS have significant similarities with IMD precipitations. The wet season‐based analysis results showed that TRMM and CHIRPS are closer to IMD precipitations than SM2RAIN‐ASCAT satellite‐precipitations. Overall TRMM and CHIRPS datasets performed well across most regions in India, while SM2RAIN‐ASCAT dataset has performed poorly in India, especially for extreme precipitation cases. Q–Q plots show that each satellite‐based precipitation dataset captured most of extreme cases in different quantile intervals with respect to IMD precipitation; however, SM2RAIN‐ASCAT has slightly under‐performed at many regions in India.

In vitro evaluation to intensify the differential morphogenetic response through plant growth regulators and antibiotic supplementation in sugarcane - Devendra Kumar; Rakesh Singh Sengar; Nisha Malik; Manoj Kumar Yadav; Shalani Gupta; Pooran Chand; Gopal Singh; Pushpendra Kumar (Plant Physiology Reports, 2020)

Genetics of yield, abiotic stress tolerance and biofortification in wheat (Triticum aestivum L.) - Pushpendra Kumar Gupta; Harindra Singh Balyan; Shailendra Sharma; Rahul Kumar (Theoretical and Applied Genetics, 2020)

Prediction of voltage required for nonthermal plasma based diesel exhaust treatment for removal of nitrogen oxides - Srikanth Allamsetty; Sankarsan Mohapatro; Pushpendra Kumar (Environmental Science and Pollution Research, 2020)

Stability analysis of underground pillar in the presence of overlying dump: a case study - Pushpendra Sharma; Amit Kumar Verma; Pradeep Gautam (Arabian Journal of Geosciences, 2020)

QTL analysis and fine mapping of a QTL for yield-related traits in wheat grown in dry and hot environments - Habtamu Tura; James Edwards; Vijay Gahlaut; Melissa Garcia; Beata Sznajder; Ute Baumann; Fahimeh Shahinnia; Matthew Reynolds; Peter Langridge; Harindra Singh Balyan; Pushpendra K. Gupta; Thorsten Schnurbusch; et al. (Theoretical and Applied Genetics, 2020)
Genetic control of grain yield and phenology was examined in the Excalibur/Kukri doubled haploid mapping population grown in 32 field experiments across the climatic zones of southern Australia, India and north-western Mexico where the wheat crop experiences drought and heat stress. A total of 128 QTL were identified for four traits: grain yield, thousand grain weight (TGW), days to heading and grain filling duration. These QTL included 24 QTL for yield and 27 for TGW, showing significant interactions with the environment ( Q * E ). We also identified 14 QTL with a significant, small main effects on yield across environments. The study focussed on a region of chromosome 1B where two main effect QTL were found for yield and TGW without the confounding effect of phenology. Excalibur was the source of favourable alleles: QYld.aww - 1B.2 with a peak at 149.5–150.1 cM and QTgw.aww - 1B at 168.5–171.4 cM. We developed near isogenic lines (NIL) for the interval including QYld.aww - 1B.2 and QTgw.aww - 1B and evaluated them under semi-controlled conditions. Significant differences in four pairs of NIL were observed for grain yield but not for TGW, confirming a positive effect of the Excalibur allele for QYld.aww - 1B.2 . The interval containing QYld.aww - 1B.2 was narrowed down to 2.9 cM which corresponded to a 2.2 Mbp genomic region on the chromosome 1B genomic reference sequence of cv. Chinese Spring and contained 39 predicted genes.

Pharmacognostic Evaluation and Pharmacological Validation of Sphaeranthus indicus DC - Surabhi Tiwari; Pushpendra Kumar Shukla; Akanksha Srivastava; Manish Kumar; Ankita Misra; Sharad Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Hybrid wheat: past, present and future - Pushpendra Kumar Gupta; Harindra Singh Balyan; Vijay Gahlaut; Gautam Saripalli; Bijendra Pal; Bhoja Raj Basnet; Arun Kumar Joshi (Theoretical and Applied Genetics, 2019)

Validation of QTL for grain weight using MAS-derived pairs of NILs in bread wheat (Triticum aestivum L.) - Supriya Kumari; Reyazul Rouf Mir; Sandhya Tyagi; Harindra Singh Balyan; Pushpendra Kumar Gupta (Journal of Plant Biochemistry and Biotechnology, 2019)

Molecular diversity of Papaya ringspot virus in India: genetic recombination and mutations between the isolates from different hosts and geo-climatic locations are role players in virus evolution - Y. B. Basavaraj; Ashwini Kumar; Rakesh Kumar Jain; Pushpendra Kumar; B. Parameswari; Jai Prakash (Indian Phytopathology, 2019)

Genetic diversity and population structure analysis of Asian and African aromatic rice (Oryza sativa L.) genotypes - Anurag Mishra; Pushpendra Kumar; Md. Shamim; Kapil K. Tiwari; Parveen Fatima; Deepti Srivastava; Rajendra Singh; Prashant Yadav (Journal of Genetics, 2019)

Resistance to ETEC F4/F18–mediated piglet diarrhoea: opening the gene black box - Rebeka Sinha; Nihar Ranjan Sahoo; Kush Shrivastava; Pushpendra Kumar; Salauddin Qureshi; Ujjwal Kumar De; Amit Kumar; Gandham Venkata Papa Pydi Siva Ravi Kumar; Bharat Bhushan (Tropical Animal Health and Production, 2019)

In silico prediction of short hairpin RNA and in vitro silencing of activin receptor type IIB in chicken embryo fibroblasts by RNA interference - P. Guru Vishnu; T. K. Bhattacharya; Bharat Bhushan; Pushpendra Kumar; R. N. Chatterjee; Chandan Paswan; K. Dushyanth; D. Divya; A. Rajendra Prasad (Molecular Biology Reports, 2019)

Impact assessment of meteorological drought on rainfed agriculture using drought index and NDVI modeling: a case study of Tikamgarh district, M. P., India - Pushpendra Singh Rajpoot; Ajay Kumar (Applied Geomatics, 2019)

Cloning and characterization of Bubaline mammary miRNAs: An in silico approach - Krishnadeo Ankush Khade; Manjit Panigrahi; Sheikh Firdous Ahmad; Anuj Chauhan; Pushpendra Kumar; Bharat Bhushan (Molecular Biology Reports, 2019)

A comprehensive review on water-emulsified diesel fuel: chemistry, engine performance and exhaust emissions - Amit Jhalani; Dilip Sharma; Shyam Lal Soni; Pushpendra Kumar Sharma; Sumit Sharma (Environmental Science and Pollution Research, 2019)

Wheat cytogenetics and cytogenomics: the present status - Pushpendra K. Gupta; Neeraj K. Vasistha (The Nucleus, 2018)

Genetics of Fe, Zn, β-carotene, GPC and yield traits in bread wheat (Triticum aestivum L.) using multi-locus and multi-traits GWAS - Jitendra Kumar; Gautam Saripalli; Vijay Gahlaut; Neha Goel; Prabina Kumar Meher; Kaushlesh Kumar Mishra; Prafulla Chandra Mishra; Deepmala Sehgal; Prashant Vikram; Carolina Sansaloni; Sukhwinder Singh; Pradeep Kumar Sharma; et al. (Euphytica, 2018)

QTL mapping for some grain traits in bread wheat (Triticum aestivum L.) - Supriya Kumari; Vandana Jaiswal; Vinod Kumar Mishra; Rajneesh Paliwal; Harindra Singh Balyan; Pushpendra Kumar Gupta (Physiology and Molecular Biology of Plants, 2018)

Stability assessment of jointed rock slope with different crack infillings under various thermomechanical loadings - Pushpendra Sharma; Amit Kumar Verma; Anil Negi; Manish Kumar Jha; Pradeep Gautam (Arabian Journal of Geosciences, 2018)

Simplified SMA-inspired 1-parameter SCS-CN model for runoff estimation - Sangeeta Verma; Pushpendra Kumar Singh; Surendra Kumar Mishra; Sanjay Kumar Jain; Ronny Berndtsson; Anju Singh; Ravindra Kumar Verma (Arabian Journal of Geosciences, 2018)

Biology of B. sorokiniana (syn. Cochliobolus sativus) in genomics era - Pushpendra K. Gupta; Neeraj K. Vasistha; Rashmi Aggarwal; Arun K. Joshi (Journal of Plant Biochemistry and Biotechnology, 2017)

Stable carbon and oxygen isotope study on benthic foraminifera: Implication for microhabitat preferences and interspecies correlation - Ajoy K Bhaumik; Shiv Kumar; Shilpi Ray; G K Vishwakarma; Anil K Gupta; Pushpendra Kumar; Kalachand Sain (Journal of Earth System Science, 2017)

Notes on the typification of four Himalayan aconites - Priyanka Agnihotri; Danish Husain; Pushpendra Katiyar; Tariq Husain (Kew Bulletin, 2016)

Transcription factors involved in drought tolerance and their possible role in developing drought tolerant cultivars with emphasis on wheat (Triticum aestivum L.) - Vijay Gahlaut; Vandana Jaiswal; Anuj Kumar; Pushpendra Kumar Gupta (Theoretical and Applied Genetics, 2016)

Homology modeling of chemokine CCR7, molecular docking, and in vitro studies evidenced plausible immunotherapeutic anticancer natural compounds - Pushpendra Singh; Ravi Shankar Singh; Alka Rani; Felix Bast (Medicinal Chemistry Research, 2016)

AGPase: its role in crop productivity with emphasis on heat tolerance in cereals - Gautam Saripalli; Pushpendra Kumar Gupta (Theoretical and Applied Genetics, 2015)

High-throughput virtual screening, identification and in vitro biological evaluation of novel inhibitors of signal transducer and activator of transcription 3 - Pushpendra Singh; Felix Bast (Medicinal Chemistry Research, 2015)

Stage-specific reprogramming of gene expression characterizes Lr48-mediated adult plant leaf rust resistance in wheat - Raman Dhariwal; Vijay Gahlaut; Bhaganagare R. Govindraj; Dharmendra Singh; Saloni Mathur; Shailendra Vyas; Rajib Bandopadhyay; Jitendra Paul Khurana; Akhilesh Kumar Tyagi; Kumble Vinod Prabhu; Kunal Mukhopadhyay; Harindra Singh Balyan; et al. (Functional & Integrative Genomics, 2015)

Chromosome mapping of four novel mutants in bread wheat (Triticum aestivum L.) - Priyanka Agarwal; Vandana Jaiswal; Sachin Kumar; Harindra Singh Balyan; Pushpendra Kumar Gupta (Acta Physiologiae Plantarum, 2015)

In silico molecular docking study of natural compounds on wild and mutated epidermal growth factor receptor - Pushpendra Singh; Felix Bast (Medicinal Chemistry Research, 2014)

A multi-step phosphorelay two-component system impacts on tolerance against dehydration stress in common wheat - Vijay Gahlaut; Saloni Mathur; Raman Dhariwal; Jitendra P. Khurana; Akhilesh K. Tyagi; Harindra S. Balyan; Pushpendra K. Gupta (Functional & Integrative Genomics, 2014)

Polymorphism of cytokine and innate immunity genes associated with bovine brucellosis in cattle - Om Prakash; Amit Kumar; Arvind Sonwane; Rajesh Rathore; Ran Vir Singh; Anuj Chauhan; Pushpendra Kumar; R. Renjith; Ramji Yadav; Ashish Bhaladhare; Mohd Baqir; Deepak Sharma (Molecular Biology Reports, 2014)

Multitargeted molecular docking study of plant-derived natural products on phosphoinositide-3 kinase pathway components - Pushpendra Singh; Felix Bast (Medicinal Chemistry Research, 2014)

Polyamine metabolism and lipoxygenase activity during Fusarium oxysporum f. sp. ricini -Castor interaction - Somnath D. Mhaske; Mahesh Kumar Mahatma; Sanjay Jha; Pushpendra Singh; Taslim Ahmad (Physiology and Molecular Biology of Plants, 2013)

New molecular scaffolds for the design of Alzheimer’s acetylcholinesterase inhibitors identified using ligand- and receptor-based virtual screening - Nitin Chitranshi; Shipra Gupta; Pushpendra Kumar Tripathi; Prahlad Kishore Seth (Medicinal Chemistry Research, 2013)

Targeted spatio-temporal expression based characterization of state of infection and time-point of maximum defense in wheat NILs during leaf rust infection - Dharmendra Singh; Govindraj Bhaganagare; Rajib Bandopadhyay; Kumble Vinod Prabhu; Pushpendra Kumar Gupta; Kunal Mukhopadhyay (Molecular Biology Reports, 2012)

QTL identification for molecular breeding of fibre yield and fibre quality traits in jute - Moumita Das; Sumana Banerjee; Niladri Topdar; Avijit Kundu; Reyazul Rouf Mir; Debabrata Sarkar; Mohit K. Sinha; Harindra S. Balyan; Pushpendra K. Gupta (Euphytica, 2012)

Development of SSR markers and construction of a linkage map in jute - MOUMITA DAS; SUMANA BANERJEE; RAMAN DHARIWAL; SHAILENDRA VYAS; REYAZUL R. MIR; NILADRI TOPDAR; AVIJIT KUNDU; JITENDRA P. KHURANA; AKHILESH K. TYAGI; DEBABRATA SARKAR; MOHIT K. SINHA; HARINDRA S. BALYAN; et al. (Journal of Genetics, 2012)

Development of large-scale AFLP markers in jute - Moumita Das; Sumana Banerjee; Niladri Topdar; Avijit Kundu; Debabrata Sarkar; Mohit K. Sinha; Harindra S. Balyan; Pushpendra K. Gupta (Journal of Plant Biochemistry and Biotechnology, 2011)

Manipulation of Spontaneous Emission Dynamics of Organic Dyes in the Porous Silicon Matrix - Abhinandan Makhal; Pushpendra Kumar; Peter Lemmens; Samir Kumar Pal (Journal of Fluorescence, 2010)

Effect of capsaicin on ligand binding activity of the hippocampal serotonin1A receptor - Rajesh Prasad; Pushpendra Singh; Amitabha Chattopadhyay (Glycoconjugate Journal, 2009)

Identification of SSR markers associated with seed coat permeability and electrolyte leaching in soybean - R. K. Singh; R. K. Raipuria; V. S. Bhatia; Anita Rani; Pushpendra; S. M. Husain; C. Tara Satyavathi; G. S. Chauhan; T. Mohapatra (Physiology and Molecular Biology of Plants, 2008)

A preliminary genetic analysis of fibre traits and the use of new genomic SSRs for genetic diversity in jute - Reyazul R. Mir; Sachin Rustgi; Shailendra Sharma; Ravinder Singh; Aakash Goyal; Jitendra Kumar; Anupama Gaur; Akhilesh K. Tyagi; Haseena Khan; Mohit K. Sinha; Harindra S. Balyan; Pushpendra Kumar Gupta (Euphytica, 2008)

Molecular approaches for improvement of medicinal and aromatic plants - Jitendra Kumar; Pushpendra Kumar Gupta (Plant Biotechnology Reports, 2008)

GIS based spatial data analysis for landslide susceptibility mapping - S. Sarkar; D. P. Kanungo; A. K. Patra; Pushpendra Kumar (Journal of Mountain Science, 2008)

QTL analysis for some quantitative traits in bread wheat - Kumar Gupta Pushpendra; Singh Balyan Harindra; Laxminarayan Kulwal Pawan; Kumar Neeraj; Kumar Ajay; Rouf Mir Reyazul; Mohan Amita; Kumar Jitendra (Journal of Zhejiang University-SCIENCE B, 2007)

QTL analysis for grain weight in common wheat - Neeraj Kumar; Pawan L. Kulwal; Anupama Gaur; Akhilesh K. Tyagi; Jitendra P. Khurana; Paramjit Khurana; Harindra S. Balyan; Pushpendra K. Gupta (Euphytica, 2006)

Physical molecular maps of wheat chromosomes - Aakash Goyal; Rajib Bandopadhyay; Pierre Sourdille; Takashi R. Endo; Harindra S. Balyan; Pushpendra K. Gupta (Functional & Integrative Genomics, 2005)

Gene networks in hexaploid wheat: interacting quantitative trait loci for grain protein content - Pawan Kulwal; Neeraj Kumar; Ajay Kumar; Raj Kumar Gupta; Harindra Singh Balyan; Pushpendra Kumar Gupta (Functional & Integrative Genomics, 2005)

Linkage disequilibrium and association studies in higher plants: Present status and future prospects - Pushpendra K. Gupta; Sachin Rustgi; Pawan L. Kulwal (Plant Molecular Biology, 2005)

Characterization of microsatellites and development of chromosome specific STMS markers in bread wheat - Rajeev K. Varshney; Alok Kumar; Harindra S. Balyan; Joy K. Roy; Manoj Prasad; Pushpendra K. Gupta (Plant Molecular Biology Reporter, 2000)